Peran Guru Dalam Mengelola Kelas di Lingkungan Sekolah Dasar Negeri Magersari 2 Kota Magelang - Pingkan Dina Putriani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine how the role of teachers in elementary schools. Thisresearch is a qualitative researchThe informant of this research is the fourth grade teacher of SDN Magersari 2Data collection techniques are observation and interviewsThe result of the research is classroom managementdone by the teacher first arrange the students who are in theclass, namely by making a class organizational structure, seating arrangements,decorations in the classroom, and cleanliness in the classroom. The teacher supervisesthe implementationthe task of each student who is located in the class organization.After that proceed with the application of class management